Synthesis of automatic control system of industrial steam-water heating unit - Степанець, Олександр Васильович; Ущаповський, Андрій Павлович (Eastern-European Journal of Enterprise Technologies, 2015)
The paper presents the research of the steam heating unit as the automation object. The heating unit is a complex engineering system with an increased exploitation risk, caused by using high-parameter water steam. The paper describes the synthesis procedure of the automatic control system from the problem statement and object study to a description of the simulation results. The list of the main system process variables with the factors that influence the process course in relation to the block diagram of the heating point was presented. The process features, which are typical for steam plants were indicated. The experimental transients, obtained during the commissioning by influencing on the main process variables on the part of related control bodies were given. The processed data are summarized in the form of mathematical models of individual heating unit sections and represented by transfer functions. Based on the data obtained, the structure of the automatic control system was proposed and settings of automatic controllers that ensure the preset quality parameters were calculated. The description of contour control algorithms and interaction of individual equipment items that increase the system efficiency was given.